Electrochemical supercapacitors: from mechanism understanding to multifunctional applications - Chen, Jingwei (2022)
Electrochemical supercapacitors (SC) with high power and long cycle life have been extensively studied and applied in certain areas. However, a majority of the efforts have been devoted to developing SCs with improved performance through novel electrode/electrolytes design. The full mechanistic understanding of SCs based on different electrode materials has not yet been realized. In addition, exploration of new functions for SCs to widen their applications must be accelerated. In this essay, the use of advanced characterization methods (in situ X-ray diffraction, in situ X-ray scattering, in situ atomic force microscopy, in situ nuclear magnetic resonance, in situ Raman/infrared spectroscopy, electrochemical quartz crystal microbalance, scanning electrochemical microscopy, etc.) to unveil the electrochemical process of SCs from different aspects will be discussed. The working principles, information to be extracted, and case studies of respective methods will be presented. The multipronged mechanism studies of electrode properties inspire and enable exploration of extra functions within the same electrochemical SCs. Realization of mechanically deformable, low-temperature, color tunable, self-healable, and self-chargeable SCs; integrated SC-sensors; and SC-actuators with adoption of new electrode/electrolyte/current collectors/configurations are showcased. The remaining issues hindering the wide exploitation of SCs and the future development trend of SCs are also discussed.